Flipped Classroom Effects on Grade 9 Students’ Critical Thinking Skills, Psychological Stress, and Academic Achievement - Atwa, Zaher; Sulayeh, Yaman; Abdelhadi, Ahmad; Jazar, Hazem Abu; Eriqat, Samah (International Journal of Instruction, 2022)
Flipped classroom is a recent trend in educational technology that tends to improve students learning. The purpose of this study is to examine the effectiveness of flipped classroom on grade 9 students' critical thinking skills, psychological stress and academic achievement in four subjects: Science, Math, IT and English. Quasi-experimental method was used in this study with pretest- posttest design for quantitative data, and the thematic analysis approach for qualitative data. The respondents are 16 teachers and 385 students from 4 public male and female schools. The study was conducted during the second semester 2019. The video lessons that developed or selected from internet were presented on closed Facebook group per subject for students to view and prepare before coming to classroom session. Seven research tools were prepared: open questionnaire tool for teachers and six research tools for students were prepared and conducted twice for experimental and control groups: before and after flipped classroom implementation. The tools were critical thinking skills test, psychological stress questionnaire and academic achievement test per subject. Descriptive and inferential analyses were used. The flipped classroom implementation results in statistically significant difference at the level of significance ([alpha] <0.05) between controlled and experimental groups in favor of the latter one in critical thinking skills, Math achievement and psychological stress.